Taking Sides : (McGraw-Hill Contemporary Learning Series, 2006)
This debate-style reader is designed to introduce students to controversies in justice and law through readings that reflect a variety of viewpoints. Each issue is framed with an issue summary, an issue introduction, and a postscript. The Taking Sides readers feature annotated listings of selected World Wide Web sites. Taking Sides is supported by our student website, Dushkin Online